Adjuvant radiotherapy for atypical and malignant meningiomas: a systematic review. Issue 5 (May 2014) - Kaur, Gurvinder; Sayegh, Eli T.; Larson, Andrew; Bloch, Orin; Madden, Michelle; Sun, Matthew Z.; Barani, Igor J.; James, C. David; Parsa, Andrew T.
Abstract: Atypical meningiomas (AMs) and malignant meningiomas (MMs) are tumors with a lower incidence and poorer prognosis than benign meningiomas. The role of radiotherapy as an adjuvant to surgical resection, especially for AMs, is incompletely defined. In this study, the English-language literature was systematically reviewed for studies that reported tumor characteristics, treatment parameters, and clinical outcomes after adjuvant radiotherapy for AM and MM, including overall survival, progression-free survival, and/or time to recurrence or mortality. Clinical outcomes were further assessed in the context of resection status, timing of administration, and radiation dose. Outcomes after stereotactic radiosurgery were also examined. Treatment toxicity and other potential prognostic or confounding factors were appraised. Ten and 11 studies for AM and MM, respectively, met the inclusion criteria. The median 5-year progression-free survival and overall survival after adjuvant radiotherapy were 54.2% and 67.5%, respectively, for AM and 48% and 55.6% for MM. The complication rates were 11.1% for AM and 5.1% for MM. Incomplete resection and radiation dose <50 Gy conferred significantly poorer 5-year progression-free survival. Most studies were unable to demonstrate a statistically significant prognostic benefit for adjuvant radiotherapy in AM. In conclusion, adjuvant radiotherapy significantly improved local control of AMs and MMs, especially after subtotal resection. Study limitations, including inadequate statistical power, may underlie the studies' inability to demonstrate a statistically significant benefit for adjuvant radiotherapy in AM. Because these tumors preferentially recur within 5 years of surgical resection, future studies should define whether early adjuvant therapy should become part of the standard treatment paradigm for completely excised tumors.